Space weather effects over SAMA during the extreme geomagnetic storm on May 10-11, 2024: disturbances of the neutral and ionized atmosphere - Da Silva, Ligia Alves; Shi, Jiankui; Alves, Lívia R.; Resende, Laysa Cristina Araújo; Vieira, Luis Eduardo Antunes; Costa, Joaquim Eduardo Rezende; Marchezi, Jose Paulo; Agapitov, Oleksiy V.; Sibeck, David Gary; dos Santos, Angela Machado; Andrioli, Vania Fatima; Jauer, Paulo Ricardo; et al. (Frontiers in Astronomy and Space Sciences, 2025)
A complex active region in the Sun’s photosphere from 8 May 2024, produced seven halo-type Coronal Mass Ejections (CMEs) following extreme solar flares. These events generated Solar Energetic Particles (SEPs) that propagated toward Earth, culminating in an extreme geomagnetic storm (SYM-H = −497 nT) from May 10 to 13 May 2024. This study analyzes the Sun’s photosphere, interplanetary medium, inner radiation belt, and the space weather impacts on the neutral atmosphere and E and F ionospheric layers over the South Atlantic Magnetic Anomaly (SAMA) during the storm’s main phase. The first and second Interplanetary CMEs (ICMEs) reached Earth’s bow shock at 15:00 UT and 17:00 UT on May 10, respectively. The second ICME, associated with a shock, caused a significant displacement of the dayside magnetopause (∼6 Earth radii, RE) and the first solar wind Poynting flux transfer into the magnetosphere (Akasofu parameter, Epsilon ∼ 1 × 1013 W). At 18:00 UT, the third ICME and its associated shock pushed the magnetopause further to ∼5 RE and added energy to the magnetospheric budget (Epsilon ∼2.5 × 1013 W). Between 19:00 and 21:00 UT, the solar wind proton density (>40 cm-3) peaked at Earth’s bow shock, but no energy input to the magnetosphere occurred (Epsilon ∼0 W). Low-energy electron/ion fluxes vanished in the inner radiation belt. Epsilon gradually increased between 21:00 and 22:30 UT, coinciding with the onset of low-energy electron/ion injections into the inner radiation belt and substorm activity. These injections persisted after 22:30 UT, albeit limited to specific energy levels. Enhanced energetic particle precipitation (EPP) and local particle acceleration caused significant variability in electron/ion fluxes in the inner radiation belt. Increased scattering by plasma waves precipitated particles into the SAMA atmosphere, raising ionization rates and depleting ozone in the mesosphere and stratosphere. Extra ionization in the E ionospheric region further indicated auroral-like effects in this low-latitude region during the storm’s main phase.